2021
DOI: 10.1039/d1nj01953h
|View full text |Cite
|
Sign up to set email alerts
|

Cu-Doped Co3O4 microstructure as an efficient non-noble metal electrocatalyst for methanol oxidation in a basic solution

Abstract: Rational design of non-noble metal electrocatalysts is an urgent task to lower the cost of electrocatalysts for methanol oxidation reaction (MOR). Herein, mesoporous Cu-Co3O4 electrocatalysts have been prepared by using...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The decreasing current density for ANCO-3 can be attributed to its lower ECSA. As compared to Table , the MOR performance of ANCO-2 is better than in some previous studies. ,,, The oxygen evolution reaction is a competitive reaction with MOR, and the linear sweep voltammogram (LSV) curves demonstrate that the MOR curve has a much smaller potential (310 mV) than the oxygen evolution reaction (Figure e). This proves that ANCO-2 has excellent methanol response characteristics. ,, …”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…The decreasing current density for ANCO-3 can be attributed to its lower ECSA. As compared to Table , the MOR performance of ANCO-2 is better than in some previous studies. ,,, The oxygen evolution reaction is a competitive reaction with MOR, and the linear sweep voltammogram (LSV) curves demonstrate that the MOR curve has a much smaller potential (310 mV) than the oxygen evolution reaction (Figure e). This proves that ANCO-2 has excellent methanol response characteristics. ,, …”
Section: Resultsmentioning
confidence: 59%
“…Stability is one of the key factors for electrocatalysts, and it is often assessed by CA and CV methods. ,, CA tests were used to evaluate the durability of electrocatalysts toward MOR. Figure a illustrates the CA result of the obtained samples in 1.0 M KOH with 1.0 M CH 3 OH solution with an applied potential of 1.5 V vs RHE for 36,000 s. The gradual decrease in the current density is due to the gradual occupation of active sites by reaction intermediates . ANCO-2 exhibits higher stability compared with the other samples, mainly due to the following two aspects: (1) It has the highest ECSA, which can be attributed to the introduction of oxygen vacancies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that doping metal elements such as Bi, 62 W, 63 Mg, Ni, and Cu 64 in Co 3 O 4 can regulate the electronic structure to achieve the improvement of electrocatalytic properties. In 2022, Wang et al 62 investigated a monoatomic bismuth (Bi) doping strategy to confer enhanced electrocatalytic alcohol oxidation reactivity and selectivity to Co 3 O 4 .…”
Section: Summary Of Co-based Spinel Oxidesmentioning
confidence: 99%
“…Co 3 O 4 , as the support of single-atom catalysts, is also superior in electron-structure modulation to induce the adjustments for methanol adsorption behaviors and reaction pathways. , The good performance of Co 3 O 4 -supported single-atom catalysts for MOR is probably derived from the reconstructed facets via the strategies of metal doping, diverse morphology, and defect engineering. , For instance, Pt 1 –Co 3 O 4 designed and synthesized by He has preferred methanol oxidation to CO 2 . It is found that the substitutional Pt sites with a large proportion of occupied high electronic states at the Co 3 O 4 (111) facet increase the metal–support interactions and promote the co-adsorption of methanol and O 2 molecules .…”
Section: Introductionmentioning
confidence: 99%